Eight Types of Interchangeable Prosthetic Heart Valve: A Mini Review. (Global Journal of Medical Research, 2023)
Introduction Bioprostheses are prone to structural degeneration and have limited durability Implantation of a prosthetic heart valve is risky when subsequent reoperation is required to replace the worn prosthetic valve Methods A review of interchangeable prosthetic heart valve models between 1984 and 2022 Results Eight types of bioprostheses with interchangeable mechanisms intended for heart valve prosthesis implantation and rapid substitutions during reoperations aim to describe their framework s mechanical structure and increase knowledge of their coupling mechanisms These are intended to reduce the surgical risks associated with the excision of the old worn bioprosthesis and shorten the reoperation time
Keywords: heart valve diseases; heart valve prosthesis implantation; biological heart valve; bioprosthesis; reoperation